Bilateral same-session ureterorenoscopy: A feasible approach to treat pan-urinary stone disease - Bora Ãzveren (Taylor & Francis Group, 2017)
Objectives: To assess treatment effectiveness and safety of bilateral same-session ureterorenoscopy (BSSU) for the management of stone disease involving the entire urinary system. Patients and methods: We reviewed the records of 64 patients who underwent BSSU for the treatment of bilateral ureteric and/or kidney stones. Size, number, location per side, and the total burden of stones were recorded. Data on stenting, lithotripsy, and stone retrieval, and details of hospital stay and operation times were investigated. Treatment results were assessed using intraoperative findings and postoperative imaging. The outcome was considered successful in patients who were completely stone-free or who had only residual fragments of â¤2â¯mm. Results: The outcome was successful in 82.8% of the patients who received BSSU (54.7% stone-free and 28.1% insignificant residual fragments). The success rate per renal unit was 89.8%. There were no adverse events in 73.4% of the patients. The most common intraoperative complication was mucosal injury (36%). The complications were ClavienâDindo Grade I in 9.4% and Grade II in 7.8%. Grade IIIa and IIIb (9.4%) complications required re-treatments. Statistical evaluation showed no association between complication grades and stone, patient, or operation features. Stone burden had no negative impact on BSSU results. The presence of impacted proximal ureteric stones was significantly related to unsuccessful outcomes. Conclusion: BSSU is safe and effective for the management of bilateral urolithiasis. BSSU can prevent recurrent surgeries, reduce overall hospital stay, and achieve a stone-free status and complication rates that are comparable to those of unilateral or staged bilateral procedures. Keywords: Ureteroscopy, Bilateral, Kidney stones, ureter stones, Flexible ureterorenoscopy, Treatment outcomes